UTILIZING SPACE IMAGERY FOR INVESTIGATING CROP VEGETATION STATUS IN PRECISION AGRICULTURE THROUGH THE GOOGLE EARTH ENGINE CLOUD PLATFORM - Chetverikov, Borys; Babiy, Lyubov; Zayats, Iryna (European Science, 2024)
This research focuses on the application of space imagery for investigating the vegetation status of crops in precision agriculture, employing the resources of the Google Earth Engine cloud platform. The study aims to assess the potential of utilizing hig